Analisis Gaya Kepemimpinan Terhadap Motivasi Kerja Karyawan: Literature Review - Ajeng Dwilianti; Adinda Saputri; Aos Kuswandi (Jurnal Psikologi, 2025)
This study aims to examine the influence of leadership on employee work motivation within an organization. The method used is a literature review, analyzing various relevant scientific articles published within the last five years. These articles were selected based on their relevance to the topics of leadership and work motivation. The results of the study indicate that leadership has a significant impact on employee motivation, both directly and indirectly. The findings highlight that the role of a leader is crucial in shaping a supportive and collaborative work environment. This research is expected to serve as a reference for organizational leaders in developing leadership strategies that maximize employee potential and to provide a foundation for future research in various organizational contexts